1981
DOI: 10.1002/em.2860030209
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of products from coal gasification and liquefaction in the salmonella/microsome assay

Abstract: As a first step in the assessment of their possible bio-effects, coal-related materials were tested for mutagenicity in the Salmonella/microsome assay. Of three coal gasification by-products tested, only a tar was mutagenic for any of four Salmonella strains. The following liquefaction materials were mutagenic for strains TA1538, TA98, and/or TA100: A liquefaction vehicle oil and coal hydrogenation filtered liquid, separated bottoms, vacuum overhead, and vacuum bottoms. Neither powdered coal nor water produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1982
1982
1985
1985

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Test results were uniformly negative where microsomal activation was not included in the test protocol. This agrees with reports by Epler et al (14), and Schoeny et al (11) of tests on cod conversion products and residues. All subsequent tests of the organic solvent extract fractions and the second lot of samples (2277-2280) included microsomal activation.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Test results were uniformly negative where microsomal activation was not included in the test protocol. This agrees with reports by Epler et al (14), and Schoeny et al (11) of tests on cod conversion products and residues. All subsequent tests of the organic solvent extract fractions and the second lot of samples (2277-2280) included microsomal activation.…”
Section: Resultssupporting
confidence: 94%
“…Warshawsky et al (10) conducted Ames tests on a group of residuals resulting from coal gasification and liquefaction. Schoeny et al (11) reported on extension of the aforementioned study that characterized powdered coal, wastewater from a hydrogenation process, and some coal conversion waste streams. In the above two studies, vacuum bottoms, a solid residual, were found to exhibit high mutagenic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Data from studies of complex organic mixtures have indicated that all such mixtures may not have biological activities that are equal to the summed bioactivities of the components [Rao et al, 1979;Salamone et al, 1979;Schoeny, et al, 1981;Somani et al, 19811. It was decided, therefore, to assay artificial mixtures of synthetic diols, quinones, and phenols for mutagenicity.…”
Section: Mutagenicity Of Mixtures Of Metabolite Standardsmentioning
confidence: 99%